Terahertz science and technology for military and security applications - Woolard, Dwight L. (Selected topics in electronics and systems, 2007)
The inherent advantages and potential payoffs of the terahertz (THz) regime for military and security applications serve as an important driver for interest in new THz-related science and technology. In particular, the very rapid growth in more recent years is arguably most closely linked to the potential payoffs of THz sensing and imaging (THz-S & I). This book presents some of the leading fundamental research efforts towards the realization of practical THz-S & I capabilities for military and security applications. Relevant subjects include theoretical prediction and/or measurement of THz spectr.